An evaluation and review of English language pre-exposure prophylaxis websites and YouTube videos. (April 2020) - Whiteley, Laura; Healy, Meredith G; Lowery, Ashley; Haubrick, Kayla K; Brown, Larry K
Pre-exposure prophylaxis (PrEP) is a promising HIV prevention strategy in which antiretroviral medications are taken to prevent HIV infection. PrEP was approved as an HIV prevention method in the United States in 2012 for individuals aged 18 years and older. Since its approval, there has been a growing amount of online content about PrEP targeted to general, non-medical, audiences. However, this online information is under-studied and under-evaluated. Two raters catalogued and coded PrEP material written in the English language from 61 websites and 58 YouTube videos for educational content, credibility, usability, and interactivity. The online material was catalogued and searched for between September 2017 and April 2018. Online PrEP material showed deficiencies in each of these content areas, however, there is a significant amount of publicly accessible online content available about PrEP. This content could be packaged, used, and tested in a prevention intervention to improve PrEP uptake and engagement in care.